The Influence of Environmental Social Governance (ESG) Disclosure, Capital Structure, and Financial Performance on Firm Value (A Study on LQ45 Index Companies Listed on the Indonesia Stock Exchange (IDX) in 2020–2023) - Rahayu, Rina; Maryani, Neni (CV. Proaksara Global Transeduka, 2025)
The primary objective of this research is to investigate the correlation between ESG disclosure, capital structure, and financial performance on a company's value. Employing quantitative methods, the study adopts a causal approach. Instead of random sampling, a purposive sampling method is used to select 21 companies from the LQ45 index on the Indonesia Stock Exchange between 2020 to 2023, resulting in 84 data points. The findings suggest that ESG disclosure does not significantly impact firm value, while capital structure has a detrimental effect. Additionally, the study indicates that financial performance does not have an influence on firm value. The implications of this research offer valuable insights for companies seeking to enhance their ESG disclosure practices and can serve as a beneficial resource for decision-making processes for investors and management.